2020
DOI: 10.1002/jcad.12340
|View full text |Cite
|
Sign up to set email alerts
|

Personal Growth Initiative and Mental Health: A Meta‐Analysis

Abstract: Personal growth initiative (PGI) is an individual's active and intentional desire to grow in personally important areas. In the past 20 years, a body of literature has emerged examining PGI's relationship to mental health. We conducted the first meta‐analyses to synthesize this literature. Two meta‐analyses examined the relationship between PGI total scores and distress (k = 22) and wellness (k = 37). Both average effect sizes were significant. We also examined the potential impact of nine moderators. The type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 72 publications
2
12
0
Order By: Relevance
“…Personal growth initiative can buffer or reduce psychological distress influenced by an intolerant tendency to uncertainty, with a prediction level of 11.7 percent. The findings are in accordance with previous research (Ayub & Iqbal, 2012;Weigold et al, 2020;Yakunina et al, 2013). Moreover, in line with Schroder et al (2017), personal growth initiative supported by a growth mindset can prevent or reduce the effects of stressful life events.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Personal growth initiative can buffer or reduce psychological distress influenced by an intolerant tendency to uncertainty, with a prediction level of 11.7 percent. The findings are in accordance with previous research (Ayub & Iqbal, 2012;Weigold et al, 2020;Yakunina et al, 2013). Moreover, in line with Schroder et al (2017), personal growth initiative supported by a growth mindset can prevent or reduce the effects of stressful life events.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies provide an alternative to individuals' positive disposition to prevent psychological distress. Related conditions tend to be low in individuals with a positive mindset (Ayub & Iqbal, 2012;Schroder et al, 2017;Weigold et al, 2020). For people suffering a quarter-life crisis, the transition (adolescent to adulthood) is stressful, making them vulnerable to experiencing psychological distress.…”
Section: │ 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most widely used scales in studies involving college student populations are the Personal Growth Initiative Scale (PGIS) [ 21 ] and the Personal Growth Initiative Scale-II (PGIS-II) [ 5 ]. Existing research on the factors correlated with personal growth initiatives among college students indicates that individual psycho-protective factors such as self-esteem and self-efficacy have been found to correlated with college students’ personal growth initiatives [ 22 , 23 ] and have study also found that personal growth initiatives among college students are closely correlated with mental health [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are only two existing research evidence review articles on personal growth initiatives, one of which is a systematic review [ 14 ] that only introduces factors correlated to personal growth initiatives at the theoretical level and does not identify the specific level of correlation. The other one is a meta-analysis [ 24 ] that only explores the relationship between personal growth initiatives and mental health, while the extent of the correlation between personal growth initiatives and mental health was identified, it was limited to two factors (distress and well-being), with the correlated factors having very limited coverage. Obviously, both two studies have their own limitations and the above issues have not been well addressed, as well as the populations in these two studies are not college students.…”
Section: Literature Reviewmentioning
confidence: 99%